The Influence of Competence, Leadership Style, and Organizational Culture on the Performance of Employees of the Tanah Datar District Land Office - Suryanto, Dasep; Kapoor, Rishi (Journal of Applied Business Administration, 2023)
This study aims to see the effect of competence, leadership style, and organizational culture partially on employee performance and then the influence of competence, leadership style, and organizational culture together on employee performance. The population of this study was all employees of the Tanah Datar District Land Office, a total of 87 people. The sample in this study was taken from all populations, namely as many as 87 people. The data were collected using a Likert Scale model questionnaire and multiple linear regression analysis with the help of the SPSS computer program. The results of the analysis show that the competency variable, leadership style and Organizational culture partially has a positive and significant effect on the performance of the Tanah Datar District Land Office employees. Competency Variables, Leadership style, and Organizational Culture together have a positive and significant effect on the performance of the Tanah Datar District Land Office employees.